Three-dimensional spectral-spatial EPR imaging of free radicals in the heart: a technique for imaging tissue metabolism and oxygenation. - Kuppusamy, P (1994)
It has been hypothesized that free radical metabolism and oxygenation in living organs and tissues such as the heart may vary over the spatially defined tissue structure. In an effort to study these spatially defined differences, we have developed electron paramagnetic resonance imaging instrumentation enabling the performance of three-dimensional spectral-spatial images of free radicals infused into the heart and large vessels. Using this instrumentation, high-quality three-dimensional spectral-spatial images of isolated perfused rat hearts and rabbit aortas are obtained. In the isolated aorta, it is shown that spatially and spectrally accurate images of the vessel lumen and wall could be obtained in this living vascular tissue. In the isolated rat heart, imaging experiments were performed to determine the kinetics of radical clearance at different spatial locations within the heart during myocardial ischemia. The kinetic data show the existence of regional and transmural differences in myocardial free radical clearance. It is further demonstrated that EPR imaging can be used to noninvasively measure spatially localized oxygen concentrations in the heart. Thus, the technique of spectral-spatial EPR imaging is shown to be a powerful tool in providing spatial information regarding the free radical distribution, metabolism, and tissue oxygenation in living biological organs and tissues.